Securing Digital Communication: A Deep Dive into Network Security and Cryptography (International Journal of Engineering and Computer Science, 2023)
The rapid growth of digital communication has brought about unprecedented opportunities and challenges in ensuring the confidentiality and integrity of sensitive information. Network security and cryptography have emerged as indispensable fields to counteract potential threats and vulnerabilities that can compromise the security of data during transmission. This abstract provides a concise overview of the purpose, problems, design approaches, and key findings in the realm of network security and cryptography. In today's digital landscape, network security and cryptography stand as crucial safeguards for maintaining the confidentiality and integrity of information exchanged over networks. This abstract presents an overview of the purpose, challenges, design strategies, and key findings within the domains of network security and cryptography.When information travels over a computer network, it is exposed to external changes that may have malicious intentions. Most modern methods for storing and using data and code securely rely on cryptographic arrangements, such as encryption keys. Data Security is the key method of sending information securely over an untrusted network. It includes the administrator-imposed limits on which users can access networked data. Both public and private networks exist. Associations and various types of networks are related with security.